2011
DOI: 10.1021/jp2050838
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Surface Charge Transfer through Competing Long-Range Repulsive versus Short-Range Attractive Interactions

Abstract: We report a combined experimental and theoretical study of the modulation of surface charge transfer on the tetrathiafulvalene (TTF)/Au(111) interface as a function of coverage in the submonolayer regime by combining low-temperature scanning tunneling microscopy, high-resolution photoemission spectroscopy using synchrotron radiation, and density functional theory (DFT) calculations. The modulation is induced by the competition between long-range repulsive Coulombic interactions and short-range attractive hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
71
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 58 publications
7
71
1
Order By: Relevance
“…An interaction driven by a charge transfer from/to the substrate can be the origin of the repulsion between the chains, as already reported for other one dimensional molecular systems. 25,[48][49][50] A surface state mediated interaction, observed for different adatoms on Cu(111) 51,52 or for pentacene molecules on Cu(110), 53 seems not to be pertinent here, since we find a coverage-dependent average distance between the chains.…”
Section: Resultsmentioning
confidence: 68%
“…An interaction driven by a charge transfer from/to the substrate can be the origin of the repulsion between the chains, as already reported for other one dimensional molecular systems. 25,[48][49][50] A surface state mediated interaction, observed for different adatoms on Cu(111) 51,52 or for pentacene molecules on Cu(110), 53 seems not to be pertinent here, since we find a coverage-dependent average distance between the chains.…”
Section: Resultsmentioning
confidence: 68%
“…These systems show a variety of different phases, the properties of which can be tuned by the proper choice of molecules, substrates, preparation conditions, temperature, etc. It has also been realized that -in particular -the interaction between the first molecular layer and the surface is dominant for the properties of the organic films [7][8][9][10][11][12]. It determines the molecular orientation and ordering in the first layer and subsequently also the growth behavior of the entire thin film adsorbed subsequently.…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive understanding of the physical properties of metal-organic interfaces was achieved by studying the adsorption of the organic interface layer of prototype molecules, such as 3,4,9,10-perylenetetra-carboxylic-dianhydride (PTCDA) [1][2][3][4][5][6], metal phthalocyanines (MePc) [7][8][9][10][11][12][13][14][15][16], and other π -conjugated molecules [17][18][19][20] on highly crystalline (noble) metal surfaces. In many investigations it was found that the geometric structure and the electronic level alignment at these metal-organic interfaces are determined by the interactions between the molecules themselves, as well as between the molecules and the metal surface.…”
Section: Introductionmentioning
confidence: 99%